Analysis of the Effect of Guide Vane Opening Variations and Total Blades on Cross Flow Turbine Performance Using Computational Fluid Dynamic - Navis, Akbar; Suryanto, Heru; Murdanto, Putut (Universitas Negeri Malang, 2020)
Indonesia is an agrarian country that continuously produces water, so it has the potential to develop a hydroelectric power plant. Computational Fluid Dynamic (CFD) application could be used to be an economical, quick, and efficient approach to improve the engineering design and turbine performance. This research aimed to find the effect of guide vane opening variations and total blades on cross-flow turbine performance using CFD simulation. This research used experimental modelling method with ANSYS program for turbine design with 22, 24, and 26 turbine blades and guide vane opening variations of 12°, 16°, 20°, 24°, and 36°. The data were collected by reviewing the simulation results after the numerical calculation process. The results showed that the cross-flow turbine performance was improving along with the increasing guide vane opening. The optimum turbine performance (power and efficiency) was obtained at 24° opening of guide vane and 26 total blades, producing 868.53 W power with 75.16% efficiency.